Correction: Corrigendum: Regulation of monocyte cell fate by blood vessels mediated by Notch signalling - Jaba Gamrekelashvili (Nature Portfolio, 2017)
Nature Communications 7: Article number: 12597 (2016); Published: 31 August 2016; Updated: 3 May 2017 The authors inadvertently omitted Christine Häger, who was involved in the initial characterization of Notch mutant mice presented in this Article, from the author list and Author contributions statement.